The Use of Teams Games Tournament Learning Model through Wordwall Media to Improve Learning Outcomes of Pancasila Education - Gunawan, Jelita Vita; Dianasari, Dianasari; Nurkholis , Nurkholis (Journal of Educational Sciences, 2025)
This classroom action research was motivated by the low learning outcomes of class VC students at the UPTD of SD Negeri 1 Weru Lor in the Pancasila Education subject, especially in Chapter 4 "Me and My Environment". This study aims to improve student learning outcomes through the use of the Teams Games Tournament (TGT) learning model through Wordwall media. This study used the Kemmis and McTaggart classroom action research design, which consisted of two cycles, each covering the planning, implementation, observation, and reflection stages. Data were collected through observation, interviews, documentation, and written tests. The results of Cycle I showed that 11 students (38%) achieved the Minimum Completion Criteria (KKTP) with an average score of 66, while in Cycle II, 25 students (86%) achieved the criteria with an average score of 84. These results indicate a significant improvement in student learning outcomes. It can be concluded that the use of the Teams Games Tournament (TGT) learning model through Wordwall media is effective in improving the learning outcomes of Pancasila Education subjects for class VC students at UPTD SD Negeri 1 Weru Lor.